1992
DOI: 10.1037/0012-1649.28.5.821
|View full text |Cite
|
Sign up to set email alerts
|

Arousal/visual preference interactions in high-risk neonates.

Abstract: We investigated the organization of arousal and attention processes in 138 neurologically at-risk neonates by studying visual preferences when the infants were in 3 arousal conditions: less aroused (after feeding while swaddled), more aroused-internal (before feeding while unswaddled), and more aroused-external (after feeding while swaddled with 8-Hz visual stimulation before each trial). The stimuli were unpatterned light panels illuminated at temporal frequencies of 1,2,4, and 8 Hz. Four brain insult groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Structures in the ascending noradrenergic pathway are involved in the processing of vestibular input (Nishiike et al 1997, Pompeiano et al 1991, Schuerger & Balaban 1999, and so it seems possible that stimulation involved in common caregiving activities (picking up or rocking the infant) may produce changes in norepinephrine in any number of higher-order brain areas. Furthermore, it is also the case that newborns' and 1-month-old infants' visual responses to stimuli of different levels of complexity, motion, or novelty are strongly affected by manipulations of arousal, such as feeding or swaddling (Gardner & Karmel 1981, 1984Gardner et al 1992;Gardner & Turkewitz 1982;Geva et al 1999), or by prior stimulation in modalities other than vision (Gardner et al 1986). This is not the case with older infants, however.…”
Section: The Alert State In Young Infantsmentioning
confidence: 80%
“…Structures in the ascending noradrenergic pathway are involved in the processing of vestibular input (Nishiike et al 1997, Pompeiano et al 1991, Schuerger & Balaban 1999, and so it seems possible that stimulation involved in common caregiving activities (picking up or rocking the infant) may produce changes in norepinephrine in any number of higher-order brain areas. Furthermore, it is also the case that newborns' and 1-month-old infants' visual responses to stimuli of different levels of complexity, motion, or novelty are strongly affected by manipulations of arousal, such as feeding or swaddling (Gardner & Karmel 1981, 1984Gardner et al 1992;Gardner & Turkewitz 1982;Geva et al 1999), or by prior stimulation in modalities other than vision (Gardner et al 1986). This is not the case with older infants, however.…”
Section: The Alert State In Young Infantsmentioning
confidence: 80%
“…Abnormal visual disengagement in very young infants might interfere with social-communication, emotion regulation, and joint attention in HR infants Schietecatte et al, 2012;Bryson et al, 2014). For example, if an infant has trouble disengaging from a distressing stimulus to look towards a distracting event, the infant may become hyper-aroused and, overtime, develop atypical arousal regulation (Gardner et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…ASD is one of the most prevalent forms of developmental disability internationally, with current estimates at 1 in 68 (Centers for Disease Control and Prevention, 2014). Impairments to attention have often been considered to be associated or comorbid with the disorder (Keehn et al, 2013), although recent research has suggested that attentional abnormalities play more of a primary role in ASD, underlying several core features, including the impairments in emotional regulation Gardner et al, 1992;Anderson and Colombo, 2009;Garon et al, 2009), and in joint attention (Schietecatte et al, 2012;Morales et al, 2000;Mundy et al, 2007), as well as the inflexibility in behaviour (Hutt et al, 1964;Landry and Bryson, 2004;Lovaas et al, 1979;Casey et al, 1993;Townsend et al, 1996Townsend et al, , 2001Senju et al, 2004). Not surprisingly, impairments to the alerting network, the orienting network, and the executive control networks have been reported in ASD (for an overview of atypical attention in ASD using the three network model, see Keehn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the perinatal period, other investigators have found cocaine-exposed neonates to demonstrate poorer habituation (which includes reaction to the repeated presentation of a visual stimulus) on the NBAS (Eisen et al, 1991;Mayes et al, 1993), poorer orientation (Mirochnick et al, 1997;Delaney-Black et al, 1996), and to demonstrate deficits in arousal-modulated attention similar to those noted in neonates with central nervous system compromise (Gardner, Karmel, & Magnano, 1992). Similarly, abnormalities in the left hemisphere visual attention system have been implicated in a study which found that cocaine-exposed infants are slower to orient to stimuli in the right visual field (Heffelfinger, Craft, & Skyken, 1997).…”
Section: Discussionmentioning
confidence: 99%